Human Resource Competence Analysis of Artificial Intelligence In Bureau of Research and Strategy POLRI - Adi Sumirat (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid development of Artificial Intelligence technology has recently had a significant impact on various sectors of life, including in the police sector. Biro jianstra POLRI as one of the work units within the Indonesian National Police is required to be able to adapt quickly to these changes in order to be able to‪Rus provides excellent service to the community. The research method used in this study is a qualitative method with a literature study approach. Data collection is carried out through a review of relevant documents related to HR competencies and the development of Arti‪ficial Intelligence in the Birojianstra POLRI environment. The results of this study indicate that improving HR competency is an important strategy that must be carried out by Birojianstra POLRI development of Artificial Intelligence